MetS: an interactive application to identify metabolites in liquid chromatography-mass spectrometry experiments with data independent acquisition - Daniel Estevan Garcia-Niño; Liliana Lopez-Kleine; Federico Roda-Fornaguera (Dyna)
Liquid chromatography-tandem mass spectrometry (LC-MS/MS) with data-independent acquisition (DIA) enables the detection of metabolites in biological samples. However, identifying metabolites from DIA data remains challenging due to the complexity of the data. This work presents "Metabolomic Search" (MetS), a software application developed to facilitate metabolite identification in DIA experiments. The application supports filtering, correlation analysis, and similarity scoring algorithms to match DIA data to user-provided metabolite mass-to-charge ratios and fragmentation patterns. The graphical user interface is straightforward and intuitive, allowing easy data uploading, parameter configuration, and results exploration. Tests on different Solanaceae samples demonstrated successful identification of target metabolites such as scopolamine. By enabling rapid compound screening, MetS can support metabolomic based research in pharmaceutical, biotechnological, and clinical domains. The availability of this open-source tool could help address the pressing need for metabolite annotation in increasingly prevalent DIA experiments.